Omics approaches on fresh‐cut lettuce reveal global molecular responses to sodium hypochlorite and peracetic acid treatment. (11th August 2017) - Daddiego, Loretta; Bianco, Linda; Capodicasa, Cristina; Carbone, Fabrizio; Dalmastri, Claudia; Daroda, Lorenza; Del Fiore, Antonella; De Rossi, Patrizia; Di Carli, Mariasole; Donini, Marcello; Lopez, Loredana; Mengoni, Alessio; et al.
Abstract: BACKGROUND: Lettuce is a leafy vegetable that is extensively commercialized as a ready‐to‐eat product because of its widespread use in human nutrition as salad. It is well known that washing treatments can severely affect the quality and shelf‐life of ready‐to‐eat vegetables. The study presented here evaluated the effect of two washing procedures on fresh‐cut lettuce during storage. RESULTS: An omics approach was applied to reveal global changes at molecular level induced by peracetic acid washing in comparison with sodium hypochlorite treatment. Microbiological analyses were also performed to quantify total bacterial abundance and composition. The study revealed wide metabolic alterations induced by the two sanitizers. In particular, transcriptomic and proteomic analyses pointed out a number of transcripts and proteins differentially accumulated in response to peracetic acid washing, mainly occurring on the first day of storage. In parallel, different microbiota composition and significant reduction in total bacterial load following washing were also observed. CONCLUSION: The results provide useful information for the fresh‐cut industry to select an appropriate washing procedure preserving fresh‐like attributes as much as possible during storage of the end product. Molecular evidence indicated peracetic acid to be a valid alternative to sodium hypochlorite as sanitizer solution. © 2017 Society of Chemical Industry